Influence of COVID-19 on the Psychological Wellbeing of Tertiary Institution Students in Nigeria - Akorede, Seun; Ajayi, Ayodotun; Toyin, Atanda; Uwadia, Gilbert (Tanzania Journal of Science, 2021)
The outbreak of COVID-19 has led to a global lockdown, pending the time medical researchers find a vaccine for the coronavirus. This study examined if loneliness, depression and stress are influences of COVID-19 on the psychological wellbeing of tertiary institutions students in Nigeria. A descriptive research design of survey type was employed for this study. The population comprised all students of tertiary institutions in Nigeria totaling about 4,406,000. One hundred and thirty-seven (137) respondents were sampled for the study. A validated researcher developed questionnaire tested for reliability was used for the study. The data collected were analyzed using descriptive statistics. Chi-square was used to test the hypotheses. All the hypotheses were tested at 0.05 level of significance. The results revealed that loneliness, depression and stress are significant influences of COVID-19 on the psychological wellbeing (Cal χ2 val ˃ Tab χ2 val) @ 0.05 alpha level). The study concluded that loneliness, depression and stress are influences of COVID-19 on the psychological wellbeing of the students. Therefore, it was recommended that more social programmes should be organized on television as long as lockdown is active to help students out of loneliness to support the mental health and well-being of students to save them for depression. Keywords: COVID-19; psychological wellbeing; depression; loneliness; stress; tertiary